Histoire de règne de Philippe II - Prescott, William Hickling, 1796-1859; Ithier, Paul; Renson, Georges (Brussel : Lachoit, Van Mienen, 1861)
Vie de Charles-Quint à Yuste - Visite de sa soeur - Mort de Eléonore - Visite de Philippe II à Yuste